Synthesis of hydrogenated 2-benzazepin-1-ones by the addition of aryllithium intermediates to isocyanates. Issue 5 (28th March 2015) - Quick, Matthias P.; Wünsch, Bernhard
Graphical abstract: Abstract: Two routes for the synthesis of (2-bromophenyl)propionaldehyde derivatives5 and8 –10 were followed. In the first route, aldehyde4 was homologated by a Wittig reaction and the resulting α, β-unsaturated acetal5 was hydrogenated to give8 . According to the second route a Heck reaction of bromoiodobenzene6 with allyl alcohol and subsequent acetalization provided the propionaldehyde acetals8 –10 . After halogen/metal exchange at5, 8, and9, the addition to homochiral isocyanate11 provided the enantiomerically pure benzamides12 –14 . Depending on the reaction conditions dihydro- and tetrahyro-2-benzazepines15 and16 were prepared, which are potential building blocks for the synthesis of differently substituted homochiral 2-benzazepines. Abstract : 2-[2-(1, 3-Dioxolan-2-yl)ethyl]- N -[(1 R )-1-phenylethyl]benzamide: C20 H23 NO3 [ α ]D 20 = +18.0 ( c 0.86, CH2 Cl2 ) Source of chirality: ( R )-1-phenylethyl isocyanate Abstract : 2-[(1 R )-1-Phenylethyl]-2, 5-dihydro-2-benzazepin-1-one: C18 H17 NO [ α ]D 20 = +47 ( c 0.19, CH2 Cl2 ) Source of chirality: ( R )-1-phenylethyl isocyanate